Strategi Pemasaran untuk Meningkatkan Daya Saing Coffeeshop: Studi Kasus 110 Degreecafe - Annisa, Dhea; Hussiam, Aqlina Mifahul; KHARISMA, NOVA (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The research results show that the marketing strategy implemented has had a positive impact on the competitiveness of 110 degree café. Proper market segmentation, followed by product offerings that suit customer preferences, has increased customer loyalty. Strong brand positioning has differentiated 110 degree café from its competitors, while creative promotional efforts have attracted the attention of the target market. In addition, the use of social media as a communication and promotional tool has expanded reach and increased brand awareness. This research aims to analyze the effectiveness of the marketing strategy implemented by 110 Degree Café in Seturan Yogyakarta. Through a case study approach, primary data is collected through interviews with management and direct observation, while secondary data is obtained from related literature and information from the industry. Analysis is carried out through a theoretical framework involving marketing concepts, such as market segmentation, brand positioning, promotions, and social media marketing. This research makes an important contribution to the understanding of the importance of effective marketing strategies in increasing the competitiveness of coffee shops. Practical implications of this research include recommendations for improving marketing strategies, including increased focus on deeper market segmentation, product innovation, and more efficient use of social media.